Sexuality and consumption intersections and entanglements - Keller, Mario 1987-; Kirchknopf, Johann Karl; Kühschelm, Oliver 1972-; Moser, Karin 1974- (De Gruyter Oldenbourg, 2022)
In western societies today, it goes almost without saying that sex and consumption are closely related. On the one hand, there is a plethora of commercial goods and services that shape sexual desires, and practices. On the other, there are scarcely any products or services that do not lend themselves to sexually charged advertising and mass media communication. This volume focuses on forms of hybridization of these equally suggestive notions
Keywords: Kommerzialisierung; Konsum; Sexualität